Calculation of cut‐off values based on the Autoimmune Bullous Skin Disorder Intensity Score (ABSIS) and Pemphigus Disease Area Index (PDAI) pemphigus scoring systems for defining moderate, significant and extensive types of pemphigus. (1st July 2016) - Boulard, C.; Duvert Lehembre, S.; Picard‐Dahan, C.; Kern, J.S.; Zambruno, G.; Feliciani, C.; Marinovic, B.; Vabres, P.; Borradori, L.; Prost‐Squarcioni, C.; Labeille, B.; Richard, M.A.; et al.
Summary: Background: Two pemphigus severity scores, Autoimmune Bullous Skin Disorder Intensity Score (ABSIS) and Pemphigus Disease Area Index (PDAI), have been proposed to provide an objective measure of disease activity. However, the use of these scores in clinical practice is limited by the absence of cut‐off values that allow differentiation between moderate, significant and extensive types of pemphigus. Objectives: To calculate cut‐off values defining moderate, significant and extensive pemphigus based on the ABSIS and PDAI scores. Methods: In 31 dermatology departments in six countries, consecutive patients with newly diagnosed pemphigus were assessed for pemphigus severity, using ABSIS, PDAI, Physician's Global Assessment (PGA) and Dermatology Life Quality Index (DLQI) scores. Cut‐off values defining moderate, significant and extensive subgroups were calculated based on the 25th and 75th percentiles of the ABSIS and PDAI scores. The median ABSIS, PDAI, PGA and DLQI scores of the three severity subgroups were compared in order to validate these subgroups. Results: Ninety‐six patients with pemphigus vulgaris ( n = 77) or pemphigus foliaceus ( n = 19) were included. The median PDAI activity and ABSIS total scores were 27·5 (range 3–84) and 34·8 points (range 0·5–90·5), respectively. The respective cut‐off values corresponding to the first and third quartiles of the scores were 15 and 45 for the PDAI, and 17 and 53 for ABSIS. The moderate, significant and extensive subgroups were thus defined, and had distinguishing median ABSIS ( P < 0·001), PDAI ( P < 0·001), PGA ( P < 0·001) and DLQI ( P = 0·03) scores. Conclusions: This study suggests cut‐off values of 15 and 45 for PDAI and 17 and 53 for ABSIS, to distinguish moderate, significant and extensive pemphigus forms. Identifying these pemphigus activity subgroups should help physicians to classify and manage patients with pemphigus.